Knowledge, Propensity and Hesitancy among Pregnant Women in the Post-Pandemic Phase Regarding COVID-19 Vaccination: A Prevalence Survey in Southern Italy - Cristina Genovese; Carmela Alessia Biondo; Caterina Rizzo; Rosaria Cortese; Isabella La Spina; Paola Tripodi; Bruno Romeo; Vincenza La Fauci; Giuseppe Trimarchi; Vanessa Lo Prete; Raffaele Squeri (Women, 2023)
The vaccination of pregnant women against influenza and COVID-19 may reduce the risk of severe illness in both the women of this population and their babies. Although the risks of non-vaccination are more serious than the side effects, maternal immunization is still the least-used method of prevention due to a lack of information leading to concerns about the safety and efficacy of vaccines, resulting in a low prevalence rate among pregnant individuals. Our study investigates vaccination coverage and the knowledge, attitudes and perceptions of COVID-19 in pregnant women at a university hospital. A questionnaire was created with the following three scores: a vaccination propensity score, a knowledge score and a hesitancy score. The first observation in the results was the very low number of immunized women (only 4.7% received their first dose). The main barrier towards vaccination was found to be fear of adverse events. We noticed a low percentage of influenza and diphtheria tetanus pertussis vaccination compared to other studies. Vaccination propensity was higher when healthcare workers educated their patients. As immunization is a crucial part of public health policy, measuring coverage to identify gaps and monitor trends, especially for individuals considered at high risk, and developing new strategies in order to increase awareness of vaccination during pregnancy is particularly timely and relevant.